Skewed X chromosome inactivation in fraternal female twins results in moderately severe and mild haemophilia B - OKUMURA, K.; FUJIMORI, Y.; TAKAGI, A.; MURATE, T.; OZEKI, M.; YAMAMOTO, K.; KATSUMI, A.; MATSUSHITA, T.; NAOE, T.; KOJIMA, T. (Haemophilia : the official journal of the World Federation of Hemophilia, 2008)
Female carriers of haemophilia B are usually asymptomatic; however, the disease resulting from different pathophysiological mechanisms has rarely been documented in females. In this study, we investigated the mechanisms responsible for haemophilia B in fraternal female twins. We sequenced the factor IX gene (F9) of the propositus, her father, a severe haemophilia B patient and the other family members. X chromosome inactivation was assessed by the methylation‐sensitive HpaII‐PCR assay using X‐linked polymorphisms in human phosphoglycerate kinase 1 gene (PGK1) and glutamate receptor ionotropic AMPA 3 gene (GRIA3). The twins were found to be heterozygotes with a nonsense mutation (p.Arg384X) inherited from their father. The propositus, more severely affected twin, exhibited a significantly higher percentage of inactivation in the maternally derived X chromosome carrying a normal F9. The other twin also showed a skewed maternal X inactivation, resulting in a patient with mild haemophilia B. Thus, the degree of skewing of maternal X inactivation is closely correlated with the coagulation parameters and the clinical phenotypes of the twins. Furthermore, we identified a crossing‐over in the Xq25–26 region of the maternal X chromosome of the more severely affected twin. This crossing‐over was absent in the other twin, consistent with their fraternal state. Differently skewed X inactivation in the fraternal female twins might cause moderately severe and mild haemophilia B phenotypes, respectively.